Philip Roth revisited - Halio, Jay L. 1928- (Twayne's United States authors series, 1992)
Philip Roth is unquestionably one of the major literary voices of our time, one who has combined critical acclaim with a wide readership. Since the publication of Bernard F. Rodgers's Twayne study of Roth (1978), Roth's oeuvre has expanded considerably both in bulk and in range, with the publication of such major works as The Ghost Writer, The Counterlife, and Patrimony. Philip Roth Revisited is an entirely new look at this important writer's life and work. In this sensitive study Jay L. Halio interprets Roth as fundamentally a comic writer in the tradition of that great "sit-down comedian," Franz Kafka. Humor, Halio argues, is for Roth the vehicle of truth. The present volume is more than a study of a single theme in Roth's work, however for Halio gives full consideration to the many complexities of Roth's writings. Roth has always, for instance, been a writer deeply concerned with characteristically Jewish themes, often controversially so, as in his outrageously comic Portnoy's Complaint. Halio places Roth in his Jewish-American milieu, explaining both the similarities and the differences between Roth and other Jewish-American writers, and discussing the reception of Roth's work by the Jewish community. In the latter part of his career, perhaps influenced by the insistence of readers and critics on seeing the author himself in his protagonists, Roth has turned to the complex theme of the interweaving of art and autobiography a concern that has both intrigued and irritated some critics. Halio's analysis of this important element in Roth's work is perhaps the clearest available reading of a notoriously complex subject. Comic, subtle, intelligent, Philip Roth's literary art reps careful and sensitive reading. Halio's study will be valuable to students and scholars of American literature, and to general readers interested in learning about one of America's leading men of letters.